ADVANTAGES OF INTRODUCING AGROCLUSTER IN AGRICULTURE - Berdiyev Abdumalik Hakimovich; Dustova Mukhayyo Khudayberdiyevna (Research Parks Publishing LLC, 2020)
Today, the sustainable development of agriculture depends largely on increasing its competitiveness. An important factor in this direction is the establishment of agro-clusters in Uzbekistan. This article highlights the ongoing agrarian and economic reforms in the agricultural sector and the organization of agroclusters in the development of the sector, as well as the role of infrastructure in it.